PENGARUH LINGKUNGAN POLITIK DAN HUKUM TERHADAP IMPLEMENTASI PEMASARAN GLOBAL SKALA INTERNASIONAL - M.Yuda Hendrawan, Panca Syahputra, Ryan Febrianto, Bayu Lazuardi,Suhairi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Global marketing and international business are influenced by political and legal aspects, this is because politics and law can result in senders in each country having different rules and regulations. Political and legal issues always have a significant impact on global marketing. for example, the World War caused massive damage to most countries' and global economies. the majority of companies have benefited from the best political conditions, and others have fallen victim to bad political conditions. In general, political and legal issues have a significant impact on the business industry. In the context of global marketing, legal and political influences are increasingly important in the era of globalization, where companies operate in various countries with different regulations. Understanding and compliance with applicable laws in each region is the key to success in global marketing activities. Global marketing activities are influenced by government policies, political parties and international organizations. Therefore, political and legal aspects need to be a major concern for companies that want to run their business globally. By understanding and paying attention to this, companies can achieve their goals without violating regulations in various countries. This research uses a literature study methodology. The literature study method is a series of activities related to library data collection methods, taking notes and reading, and managing research materials.